Предмет: Алгебра,
автор: sofiaesko5a
Найдите значение выражения (4 + 3x) (2 - x) – (4 -3x) (2 +x), если x = - 1,5.
Ответы
Автор ответа:
1
Подставляя x = -1,5 в данное выражение, получаем:
(4 + 3x) (2 - x) – (4 -3x) (2 +x) = (4 + 3(-1,5)) (2 - (-1,5)) – (4 -3(-1,5)) (2 +(-1,5))
= (4 - 4,5) (2 + 1,5) – (4 + 4,5) (2 - 1,5)
= (-0,5) (3,5) - (9) (0,5)
= -1,75 - 4,5
= -6,25
Ответ: -6,25.
(4 + 3x) (2 - x) – (4 -3x) (2 +x) = (4 + 3(-1,5)) (2 - (-1,5)) – (4 -3(-1,5)) (2 +(-1,5))
= (4 - 4,5) (2 + 1,5) – (4 + 4,5) (2 - 1,5)
= (-0,5) (3,5) - (9) (0,5)
= -1,75 - 4,5
= -6,25
Ответ: -6,25.
Похожие вопросы
Предмет: Математика,
автор: artiomsavchuk2009
Предмет: Українська мова,
автор: marialulcak7
Предмет: Математика,
автор: aliseitjan32
Предмет: История,
автор: likasss90
Предмет: Математика,
автор: oksi6540